FT-ICR MS characterization of bio-binders for road pavement from HTL of microalgae residues. Issue 3 (June 2022) - Geantet, Christophe; Laurenti, Dorothée; Guilhaume, Nolven; Lorentz, Chantal; Borghol, Ilef; Bujoli, Bruno; Chailleux, Emmanuel; Checa, Ruben; Schramm, Sébastien; Carré, Vincent; Aubriet, Frédéric; Queffélec, Clémence
Abstract: Hydrothermal liquefaction (HTL) of microalgae-derived feedstocks into a bio-binder was investigated in the absence or presence of a catalyst. The resulting products of HTL of Scenedesmus species (sp.) residues present rheological properties close to those of a petroleum-derived bitumen. The chemical composition of the biobinder was analysed by two-dimensional gas chromatography (GCxGC-MS), gel permeation chromatography (GPC), and negative and positive-ion laser desorption/ionization FT-ICR MS to provide a complementary analysis of the biobinder and understanding of the role of catalysts. A detailed description of the heavy nitrogen compounds contained in the biobitumen is given. Graphical Abstract: ga1 Highlights: Valorization of microalgae residues by catalytic HTL. GPC, GCxGC-MS, FT-ICR MS and elemental analysis were carried out on the biocrudes. FT-ICR MS provides description of the heavy nitrogen compounds in biocrudes. Bio-binder similar to petroleum one assessed by rheological characterization.